The Task Gallery: A 3D Window Manager - Robertson, George; Dantzich, Maarten van; Robbins, Daniel; Czerwinski, Mary; Hinckley, Ken; Risden, Kirsten; Thiel, David, Vadim Gorokhovsky (CHI '00 Proceedings of the SIGCHI conference on Human Factors in Computing Systems, 2000)
The Task Gallery is a window manager that uses interactive 3D graphics to provide direct support for task management and document comparison, lacking from many systems implementing the desktop metaphor. User tasks appear as artwork hung on the walls of a virtual art gallery, with the selected task on a stage. Multiple documents can be selected and displayed side-by-side using 3D space to provide uniform and intuitive scaling. The Task Gallery hosts any Windows application, using a novel redirection mechanism that routes input and output between the 3D environment and unmodified 2D Windows applications. User studies suggest that the Task Gallery helps with task management, is enjoyable to use, and that the 3D metaphor evokes spatial memory and cognition.